Letter (copy) : re Mrs. M. Ramshaw - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0085-001 8th December, 1937. Mr. W. Lawther, Durham Miners' Offices, 1, Red Hill Villas, DURHAM. Dear Mr. Lawther, re Mrs. M/ Ramshaw. I understand that the above lady is applying for a post under the Durham County Council, and I have been asked by the Spanish Medical Aid Committee to mention her name to you as one who has rendered good work for the Committee in Spain and whom they think worthy of every consideration. Yours sincerely. Chairman. Spanish Medical Aid Committee. 292C/946/2/85